Student cheating in examinations at a Malaysian higher education institution: A case study / Sara Asmawati Shariffuddin - Shariffuddin, Sara Asmawati (2009)
This study attempts to explore cheating behavior among Malaysian students of tertiary institutions. One in particular is Terengganu Advanced Technical Institute- University College (TATiUC). Cheating techniques, preventive measures and support required by lecturers to handle cheating incidents were examined. Six former students (confirmed cheaters) and two lecturers cum administrators of TATiUC participated in the study. Data were collected by using narrative responses and interviews. The results showed that creative and innovative techniques were used to outsmart lecturers from detecting cheating occurrences. The results also showed that participants believed even though various preventive measures were implemented, they were not able to stop academic cheating entirely. However, they were able to deter cheating to a certain extent.Furthermore, it was discovered that there were variations on the implementation of the examination rules and regulations among lecturers. Finally, the study revealed that support in terms of training and courses were needed in dealing with academic dishonesty. Thus, the findings of the study may assist lecturers and administrators in dealing with students' cheating behavior and enlighten the administrators on the kinds of support that can be extended to lecturers to mitigate their struggle dealing with students' academic misconduct.